Celostna analiza vrednostne verige lesene gradnje v Franciji - Romih, Peter (Les (Ljubljana), 2024)
The wood construction industry contributes to building a circular economy, reducing emissions and storing CO2. Achieving these goals requires a strong focus on regional value chains and building an innovative ecosystem that can produce the innovative solutions needed. As part of the European Basajaun project, a comprehensive analysis of the wood construction value chain in the New Aquitaine region of France was conducted, including opportunities for reuse and recycling. This included an analysis of strategic competitive advantages in the chain, barriers to market entry, barriers to doing business, cooperation between actors, regulatory impacts, and management and coordination functions in the chain. Most importantly, emphasis was placed on identifying barriers and opportunities for integrating open innovation processes. The analysed data were collected through a literature review of secondary sources and through the qualitative method of in-depth interviews. More than half of the interviewees saw open innovation as a strong competitive advantage, but at the same time cited several barriers. We identified opportunities to improve the value chain in the areas of digitalization, resource management, the circular economy, by strengthening research and development activities, and by connecting actors in the chain. The opportunities for the further development of value chains in wood construction are therefore significant. However, the implementation of the aforementioned solutions requires coordinated regional policies and solutions at national (and European) level.
Keywords: circular economy; digitalizacija; digitalization; krožno gospodarstvo; lesena gradnja; odprto inoviranje; open innovation; value chain; vrednostna veriga; wood construction